PENGARUH PENGGUNAAN MEDIA PAPAN "JUSUN" TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA MATERI PENJUMLAHAN BERSUSUN KELAS II SDI WATUGONG - Paula Emerentiana; Maria Elisabet Dhelo; Genoveva Lise Dua Kowe (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The problem identified in the study is that second-grade students struggle with two-digit vertical addition; they tend to calculate from the front (starting with the tens digit) because they do not fully grasp the concept of vertical addition, resulting in poor learning outcomes. This study aimed to determine the effect of using the “Jusun” board as a teaching aid on students’ learning outcomes in mathematics, specifically on the topic of column addition, for second-grade students at SDI Watugong. This study was an experimental study using a one- group pretest-posttest design. The sample consisted of 10 students. Data collection techniques included observation, testing, and documentation. Data analysis techniques involved a normality test and hypothesis testing. The results showed that the mean posttest score (68) was higher than the pretest score (52); the calculated t-value was 6.332, which was greater than the critical t-value of 1.812 at a significance level of 0.05. Thus, Ho was rejected, and Hi was accepted. The use of the Jusun Board as a teaching aid had an effect on students’ learning outcomes in the mathematics subject, specifically on the topic of column addition, for second-grade students at SDI Watugong. Keywords: Jusun Board 1, Student Learning Outcomes 2, Mathematics 3